Eficiência das técnicas manual e rotatória na remoção da obturação do canal radicular: análise por microtomografia - Azevedo, Kellen Cristina Mendes (2012)
Removing filling material from root canal is directly related to endodontics retreatment success. This study aimed to assess efficiency in removing filling material from root canals by using manual and rotary techniques with stainless steel and nickel titanium ProTaper Retreatment system respectively, and extrusion of debris through the apical foramen. Thirty human lower incisors were instrumented and filled with gutta percha and sealer by using lateral condensation technique. The extrusion of debris was quantified by waxing the apex which allowed shelter debris. The samples were divided in two groups (n=15): Group I (Rotary) were filling removal was performed by ProTaper Retreatment system completed by ProTaper Universal files; Group II (Manual) were filling removal was performed by using Gates Glidden burs, Kerr and Hedstrem files associated to organic solvent Eucaliptol. Samples were scanned by micro tomography after filling and after filling removal to quantify remaining filling material in root canal and extruded debris in these two steps. Remaining filling material percentage was obtained by difference between the filling volume before and after filling removal. Statistical analyses were performed by Mann-Whitney test for remaining filling material in full root canal and by Wilcoxon test in each third (cervical, medium and apical). The significance level was established in 5%. Descriptive analyses were performed to extruded debris assessment. There was no difference between the techniques in the total remaining filling material in root canals (p = 0.689) and in the thirds (p>0.05). Cervical third showed the lowest values for remaining filling material when compared to medium (p=0.001) and apical (p=0) thirds. Seven samples showed extruded debris, five from Rotary Group (30%) and two from Manual Group (13%). According to the results it can be concluded that both techniques showed similar performance in filling material removal considering the whole root canal. Cervical third showed the lowest remaining filling material amount in the two groups. Samples in which extruded debris were observed were insufficient to show which technique produced the event in higher or lower proportion. Neither technique tested removed filling material from root canal completely.